(untitled) (Cadernos de Sociomuseologia, 2018)
This study seeks to expose and reflect the possible dialogues that can be considered between the Social Museology, or Afro-Brazilian Museology, and the Capoeira, which aims to consolidate the historical process of resistance of this art, dance, fight, game, sport and culture, adding to the struggle of several Masters of Capoeira for the recognition, appreciation and promotion of this important Afro-Brazilian Cultural Patrimony, in other words, it is a strategic positioning that has an expanded idea of the Museum, understanding that it exists from the moment the group starts the process of self-reflection about your practices, understanding them as a living and dynamic cultural patrimony and begins to relate these practices to the aspects of the operative chain of museology, developing them in its scope. In this way, the Museum and Museology are understood as tools that contribute to the preservation and valorization of the memories, stories and the cultural collection of Capoeira. This process of preservation of memories and practices has the potential to contribute, finally, to the formulation and promotion of public politics of valorization and promotion of this cultural practice. Keywords: Capoeira; Social Museology; Afro-Brazilian Museology; Cultural Patrimony